The neuronal identity bias behind neocortical GABAergic plasticity. Issue 9 (September 2015) - Allene, Camille; Lourenço, Joana; Bacci, Alberto
Highlights: Cortical circuits result from highly specific connections between inhibitory and excitatory neuron subtypes. Different neocortical principal neuron (PN) subtypes are preferentially targeted by specific basket cell classes. PNs in different cortical layers express either depression or potentiation of perisomatic inhibition. PNs relaying to subcortical areas tend to potentiate their perisomatic inhibition. PNs connecting to other cortical areas tend to depress their perisomatic inhibition. Abstract : In the neocortex, different types of excitatory and inhibitory neurons connect to one another following a detailed blueprint, defining functionally-distinct subnetworks, whose activity and modulation underlie complex cognitive functions. We review the cell-autonomous plasticity of perisomatic inhibition onto principal excitatory neurons. We propose that the tendency of different cortical layers to exhibit depression or potentiation of perisomatic inhibition is dictated by the specific identities of principal neurons (PNs). These are mainly defined by their projection targets and by their preference to be innervated by specific perisomatic-targeting basket cell types. Therefore, principal neurons responsible for relaying information to subcortical nuclei are differentially inhibited and show specific forms of plasticity compared to other PNs that are specialized in more associative functions.